Guns and roses: Educating educators through peer coaching programme (A) - TAN, Swee Liang (Institutional Knowledge at Singapore Management University, 2014)
This case is a two-part series on conflicting pedagogical philosophies, the impact of student appraisals on teaching styles and the value of Peer Coaching Programmes for faculty. Case A is set in September 2009, shortly after James Nelson, Assistant Professor at SMU, received feedback through the university’s Peer Coaching Programme. In May 2009, Nelson had made a spontaneous decision to receive guidance from Practice Associate Professor Harry Den, after having spent several months grappling with the issue of declining student rating of his teaching performance.Den’s feedback helped Nelson reflect on his teaching style. This case is highly suitable for faculty development and executive education courses. Through the case, participants will determine the effectiveness of different pedagogical philosophies and discuss how a faculty can best balance one’s own teaching philosophy with the students’ approach to learning. Participants will also understand the value and importance of Peer Coaching Programmes for faculty.